Sustainable Construction of Earth Dams: Use of Heterogeneous Material from the Dam Site - Rubén Galindo (Sustainability, 2020)
The volumes of soil required for the construction of an earth dam are usually of importance, so that, consequently, a key aspect to mitigate the negative impacts of dam construction, both from an economic and environmental point of view, is the use of materials in the vicinity of the dam location. However, this is often complicated because the existence of good quality materials with homogeneous properties, necessary for the dam core, is scarce in sites near the dam and their presence in sufficient volume for its construction is not usual. Unfortunately, using and transporting soil with good geotechnical characteristics to construct the core in a faraway location is economically and environmentally unsustainable. Therefore, the possibility of using less suitable material at the dam site as part of the core must be studied. Thus, in the present research the use of a soil of great heterogeneity in its geotechnical properties with a great dispersion of permeability is analyzed. Considering permeability as a random variable, combinations of representative values of heterogeneous soils are analyzed using their mean permeability and coefficients of variation that allow generating different lognormal distribution functions to carry out a Monte Carlo analysis. By maintaining the soil’s global heterogeneity, it was possible to study an unlimited disposition of lifts of different permeability. The statistical formulation allowed the research of the variation of the seepage flows and maximum gradients produced as a function of the variability of their mean permeability, being able to detect the factors with the greatest influence on the generation of high flows and gradients. Thus, it was possible to verify how high gradients were obtained for situations in which the seepage flow rates were moderate and low; the highest maximum gradients were observed in the lowest lifts of the dam core. In addition, based on the results of the Monte Carlo analysis, design charts have been developed for flow rates and maximum gradients, dependent on the mean permeability and the coefficient of variation, which allow judging whether heterogeneous material can be used, under conditions of safety, for the construction of the core of a dam.